A UHPLC-MS-MS Method for the Determination of 84 Drugs of Abuse and Pharmaceuticals in Blood. Issue 1 (5th May 2020) - Orfanidis, Amvrosios; Gika, Helen G; Theodoridis, Georgios; Mastrogianni, Orthodoxia; Raikos, Nikolaos
Abstract: The analysis of blood samples for forensic or clinical intoxication cases is a daily routine in an analytical laboratory. The list of 'suspect' drugs of abuse and pharmaceuticals that should be ideally screened is large, so multi-targeted methods for comprehensive detection and quantification are a useful tool in the hands of a toxicologist. In this study, the development of an ultra-high performance liquid chromatography (LC)–tandem mass spectrometry (MS-MS) method is described for the detection and quantification of 84 drugs and pharmaceuticals in postmortem blood. The target compounds comprise pharmaceutical drugs (antipsychotics, antidepressants, etc.), some of the most important groups of drugs of abuse: opiates, cocaine, cannabinoids, amphetamines, benzodiazepines and new psychoactive substances. Sample pretreatment was studied applying a modified Mini-QuEChERS single step, and the best results were obtained after adding a mixture of 20 mg MgSO4, 5 mg K2 CO3 and 5 mg NaCl together with 600 μL of cold acetonitrile in 200 μL of sample. After centrifugation, the supernatant was collected for direct injection. LC–MS analysis took place on a C18 column with a gradient elution over 17 min. The method was found to be selective and sensitive, offering limits of detection ranging from 0.01 to 9.07 ng/mL. Validation included evaluation of limit of quantification, recovery, carryover, matrix effect, accuracy and precision of the method. The method performed satisfactorily in relation to established bioanalytical criteria and was therefore applied to the analysis of blood obtained postmortem from chronic drug abusers, offering unambiguous identification and quantitative determination of drugs in postmortem blood.